Epidemiology of Human Congenital Malformations - Källén, Bengt. (Springer International Publishing : Imprint: Springer, 2014)
The subject of this book is to describe the occurrence of congenital malformations among children born and what risk factors exist. Population data are presented for a number of malformations, ascertained with the use of data from the Swedish national health registers for the period 1998-2010 corresponding to some 1.3 million births, together with prospectively collected information on a group of exposures of possible interest. The structure of the analysis is such that it excludes studies of, for instance, nutrition, alcohol or street drug use and many other lifestyle factors where prospective information or independent register information is difficult or impossible to obtain. Epidemiology of Human Congenital Malformations culminates with a discussion on how the presence of malformations can be explained and various possibilities for the prevention of birth defects. Moreover, it will include a series of instructions on how to read epidemiological literature in this field making it an essential resource both for those currently working in the field of reproductive epidemiology or those intending to enter it. It will additionally be useful for doctors working with malformations, either as obstetricians, neonatologists or pediatricians.